Measuring Cultural Effectiveness in Occupational Therapy and Physical Therapy: A Scoping Review. - Shin, Julia; Bekmuratova, Sarbinaz; Nesbit, Jamie; Han, Inhyun; Tung, Allison; Ortiz, Jordan; Wright, Tyler; Chamoun, Sarah; Bergjord, Judith (American Journal of Occupational Therapy)
Importance: Promoting culturally effective care is a pressing matter for occupational therapy and physical therapy practitioners. Despite the recent advancements, how cultural effectiveness is measured in the rehabilitation context remains elusive. Objective: To characterize the instruments used to assess cultural effectiveness in the recent occupational therapy and physical therapy literature. Data Sources: Database searches were conducted in Academic Search Premier, CINAHL, MEDLINE, and PsycINFO. Additional hand searches were performed of key articles and textbooks. Study Selection and Data Collection: Included articles were (1) published in English in the United States between January 2010 and June 2022, (2) peer reviewed, and (3) methodologically examined or included outcome measures that assessed cultural effectiveness in occupational therapy and physical therapy contexts. Findings: Seven articles met the inclusion criteria, and six distinct instruments were identified. All of the assessments were self-administered and varied in theoretical foundation, conceptualization, and operationalization. The three most common cultural domains were attitude, knowledge, and skills. Of 249 items pooled across the instruments, only one assessed a provider's ability to engage in continuous critical reflection. Conclusions and Relevance: The inconsistencies observed in measuring cultural effectiveness may limit advancement and translation of knowledge in occupational therapy and physical therapy. In addition to the need for client-administered assessments, further research is warranted to explore how self-reflection can catalyze the lifelong process of becoming culturally effective. Plain-Language Summary: Grounded in the Cultural Effectiveness Model, this study identified assessments that can be used by occupational therapy and physical therapy practitioners to measure and monitor their cultural effectiveness. This review identifies assessments that can be used by occupational therapy practitioners to measure and monitor their cultural effectiveness.